2016
DOI: 10.3389/fpls.2016.00166
|View full text |Cite
|
Sign up to set email alerts
|

Two LcbHLH Transcription Factors Interacting with LcMYB1 in Regulating Late Structural Genes of Anthocyanin Biosynthesis in Nicotiana and Litchi chinensis During Anthocyanin Accumulation

Abstract: Anthocyanin biosynthesis requires the MYB-bHLH-WD40 protein complex to activate the late biosynthetic genes. LcMYB1 was thought to act as key regulator in anthocyanin biosynthesis of litchi. However, basic helix-loop-helix proteins (bHLHs) as partners have not been identified yet. The present study describes the functional characterization of three litchi bHLH candidate anthocyanin regulators, LcbHLH1, LcbHLH2, and LcbHLH3. Although these three litchi bHLHs phylogenetically clustered with bHLH proteins involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 62 publications
(100 reference statements)
7
71
0
Order By: Relevance
“…Based on our previously published results, LcMYB1 might play major roles in the MBW complex determining anthocyanin accumulation in litchi (Lai et al, 2014). Recently, two LcbHLH TFs interacting with LcMYB1 in regulating late structural genes of anthocyanin biosynthesis in litchi during anthocyanin accumulation has been reported (Lai et al, 2016). In the present study, to explore interaction of LcSPL1/2 with LcMYB1 or LcbHLH1/2/3, the Y2H has been employed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our previously published results, LcMYB1 might play major roles in the MBW complex determining anthocyanin accumulation in litchi (Lai et al, 2014). Recently, two LcbHLH TFs interacting with LcMYB1 in regulating late structural genes of anthocyanin biosynthesis in litchi during anthocyanin accumulation has been reported (Lai et al, 2016). In the present study, to explore interaction of LcSPL1/2 with LcMYB1 or LcbHLH1/2/3, the Y2H has been employed.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no interaction between LcSPL1/2 and LcbHLL1/2/3 ( Figure 6 ). Recently, LcbHLH1/3 interacting with LcMYB1 in regulating late structural genes of anthocyanin biosynthesis in Nicotiana and Litchi has been reported (Lai et al, 2016). In previous study, SPL9 was reported to destabilize the MBW complex to repress anthocyanin biosynthesis (Gou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast the vegetative growth and seed set of the MoroMybA as well as the PamMybA transgenic lines were not noticeably different than wild type suggesting that they are suitable candidates for biotech applications. These results further indicate that there is no requirement for the presence of an exogenous bHLH partner for the plum MYBA.1 and MYBA.5 transcription factors to achieve full functionality in this heterologous system, unlike other MYBs from cherry plum, litchi and apple (Lai et al., 2016; Espley et al., 2007; Li et al., 2007; Takos et al., 2006). …”
Section: Resultsmentioning
confidence: 99%